SCREENING FOR POTENTIAL NON-COMMUNICABLE DISEASES IN THE PALU CITY AS A POST-DISASTER AREA - Stefiani Bengan Laba; Muhammad Jusman Rau; Marselina Marselina; Nurul Vida Royana; Relin Meliyana; Uswatun Hazanah (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2025)
Non-communicable diseases have an impact on many aspects of life. Hyperuricemia is one of the non-communicable diseases. In addition to gout, anaemia is one of the problems experienced by many Indonesian people. Anaemia is a condition in which the number of red blood cells or hemoglobin concentration is less than the normal limit. The purpose of this service is to carry out uric acid and hemoglobin screening in the community in the Palu city area as a post-disaster area. The benefit of this community service activity is that the community can find out the levels of uric acid and hemoglobin from the community so that they can take steps related to the results of the examination. The method used is screening in the form of uric acid and hemoglobin examinations, and also personal counselling in the form of presentations related to the results of the examination and also follow-up suggestions. Participants in this service are people in the Palu city area.